Aggressive behaviours on peer social relationship of students with hearing impairment in Federal College of Education (Special), Oyo, Nigeria - Adebisi, Rufus Olanrewaju; Yakubu , Doris Gomos (Research Journal in Advanced Social Sciences, 2020)
This study investigated the aggressive behaviours on peer social relationship of students with hearing impairment. The purpose of the study was to determine the nature of aggression on peer social relationship of students with hearing impairment. A self-structured questionnaire was used to gather relevant data. The sample for the study consisted of one ninety (90) respondents. Three (3) research questions were raised to guide the study. The data collected were analyzed using, simple percentage method, mean and standard deviation. Based on the data generated and results obtained from the data analyzed, the findings revealed that hearing loss can create barriers in communication between children, thus adversely affect the quality and quantity of peer interaction of students with hearing impairment with their peers. The findings of the study also revealed that learners with hearing impairment have lower social status and report more loneliness than do hearing children. The study recommended among others that there was need to address the aggressive behavior among students with hearing impairment at schools levels. The classroom implication of the study was that the school should arrange counseling services for students with and without hearing impairment at school level to provide them psychotherapy for relaxation from aggressive behavior.